The genesis of strategy in new ventures: escaping the constraints of founder and team knowledge - Fern, Michael J.; Cardinal, Laura B.; O'Neill, Hugh M. (Strategic Management Journal, 2012)
Abstract Although an entrepreneur's initial strategy choices have a critical effect on a new venture's survival, growth, and long‐term performance, few studies have explored how pre‐founding experience influences these choices. Founders who over rely on their historical industry experiences may simply replicate the strategies of legacy firms. In turn, little is known about how founders can break these experience‐based constraints, if they exist. In an empirical analysis of 120 prospective entrants in air transportation from 1995–2005 we find that a founder's past experience strongly constrains choices, and the effect depends on the form of experience and type of strategy choice. Diversity of experience, at the level of the founder and founding team, lessens these constraints. Our results have valuable implications for research in strategy and entrepreneurship. Copyright © 2011 John Wiley & Sons, Ltd.